THE ART OF MAQOM SINGING: HISTORICAL DEVELOPMENT, STYLISTIC CHARACTERISTICS AND PEDAGOGICAL FOUNDATIONS - Zafar G‘ofurov (Western European Studies, 2025)
This study examines the evolution of the art of maqom singing in Uzbekistan, focusing on its historical continuity, stylistic features, and pedagogical foundations. The maqom genre represents one of the most refined forms of traditional music, encapsulating centuries of spiritual and artistic development. The article explores how the ustoz-shogird (masterapprentice) tradition shaped the transmission of maqom performance techniques, the formation of regional schools such as Bukhara, Khorezm, and Fergana-Tashkent, and the synthesis of oral traditions with academic methods in modern institutions. Through comparative and analytical methods, this study highlights the significance of maqom singing in preserving cultural identity and its integration into modern pedagogical frameworks.
Keywords: Maqom singing; ustoz-shogird tradition; Uzbek classical music